2018
DOI: 10.1016/j.envpol.2018.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Long-term interactive effects of N addition with P and K availability on N status of Sphagnum

Abstract: Little information exists concerning the long-term interactive effect of nitrogen (N) addition with phosphorus (P) and potassium (K) on Sphagnum N status. This study was conducted as part of a long-term N manipulation on Whim bog in south Scotland to evaluate the long-term alleviation effects of phosphorus (P) and potassium (K) on N saturation of Sphagnum (S. capillifolium). On this ombrotrophic peatland, where ambient deposition was 8 kg N ha yr, 56 kg N ha yr of either ammonium (NH, N) or nitrate (NO, N) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(48 reference statements)
2
4
0
Order By: Relevance
“…Unexpectedly, long-term addition of P also reduced Sphagnum cover as well as the relative abundance of Sphagnum -associated fungi instead of alleviating the negative effect of N addition, which is inconsistent with our fourth hypothesis. This result supports the notion that there is only a limited alleviating effect of P addition on excess N ( Fritz et al, 2012 ; Chiwa et al, 2018 ), likely owing to imposed physiological stress ( Fritz et al, 2012 ). Collectively, with regard to our fourth hypothesis, we did observe that long-term N addition decreased the relative abundance of Sphagnum -associated fungi, but P addition did not alleviate the negative effect of excess N input.…”
Section: Discussionsupporting
confidence: 86%
“…Unexpectedly, long-term addition of P also reduced Sphagnum cover as well as the relative abundance of Sphagnum -associated fungi instead of alleviating the negative effect of N addition, which is inconsistent with our fourth hypothesis. This result supports the notion that there is only a limited alleviating effect of P addition on excess N ( Fritz et al, 2012 ; Chiwa et al, 2018 ), likely owing to imposed physiological stress ( Fritz et al, 2012 ). Collectively, with regard to our fourth hypothesis, we did observe that long-term N addition decreased the relative abundance of Sphagnum -associated fungi, but P addition did not alleviate the negative effect of excess N input.…”
Section: Discussionsupporting
confidence: 86%
“…Chiwa et al . ); unfortunately, this was not measured in our study. Li et al (), however, we did not find changes in P concentration either in the capitula (0–1 cm) or in the stem (1–4 cm) of S. papillosum at different P fertilization levels.…”
Section: Discussionmentioning
confidence: 63%
“…In other studies, with low P concentrations in the pore water, similarly high P concentrations in the mosses were found only after P fertilization (Chiwa et al . , Limpens et al ; Limpens et al ; Limpens & Heijmans ; Fritz et al ). As in our study, Sphagnum did not respond significantly to additional P (Li et al ; Limpens et al ) at sites with similar water P concentrations as in our experiment (0.23 mg·l −1 ) and in natural bogs in Lower Saxony (Bertram ; Lütt ).…”
Section: Discussionmentioning
confidence: 99%
“…the phosphatase enzymes, to enhance P availability , thus delaying the onset of P limitation (Marklein and Houlton 2012;Maistry et al 2015). If a higher leaf N:P ratio is indicative of N saturation diagnosed from the leaf stoichiometry in wetlands (Koerselman and Meuleman 1996;Güewell 2004;Chiwa et al, 2018), then the small increases in foliar N:P ratio of Calluna exposed to different levels of N addition without P and K even after 11-years exposure ( Figure 8a) and decreases in the N:P ratio with P and K (Figure 8b), suggest that N exposure at this site does not cause N saturation in Calluna even for the high N dose without P and K addition. Chiwa et al (2018) showed that Sphagnum tissue N concentration at this same site also increased, whereas tissue P concentrations did not, in response to N dose.…”
Section: Effects Of N Status Of Calluna On Enhanced Cnr and The Assocmentioning
confidence: 99%